ضوابط فقه الواقع المعاصر - Ubeyd, Ahmed Vecih (Fatih Sultan Mehmet Vakıf Üniversitesi, 2022)
يشهد الواقع المعاصرُ أنماطًا جديدةً من التقعيد الفقهيِّ تستدعي بيانَ الضوابط الشرعيَّةِ التي ينبغي على المجتهد اتِّباعُها أثناء الحكم على واقعةٍ مستجدَّةٍ. وفي هذا البحث أسلِّط الضوءَ على هذه الضوابطِ التي تحدِّد أسسَ التعامل مع الواقع؛ كتعليل الأحكام الشرعيَّةِ، وعدمِ مخالفة قصدِ الشارع، والموازنةِ بين المصالح والمفاسد، وغيرِها ممَّا يُظهر قيمةَ الاجتهاد الفقهيِّ، وصلاحيةَ الشريعة لكل زمانٍ ومكانٍ. وخلَص البحث إلى حقيقةٍ هامَّةٍ تتمثَّل في تنزيل الوقائع المستجدَّةِ على الأصول الشرعيَّة بعيدًا عن ليِّ أعناق النصوص، فالواقعُ ليس حاكمًا للنصوص، ولا ضابطًا لها؛ بل هو يخضع لها ويُنزّل عليها.َ كما أنَّهُ يجب تحقيق الارتباطِ الوثيق بين الموروث الفقهيِّ والواقع المعاصر عبرَ معادلةٍ متوازنةٍ لا تهز الثوابتَ ولا توقف تجدُّد الحياة، واعتمادِ المنهج الوسط من خ لل التوفيق بين ا الظاهر والباطن، وإظهارِ أنَّ الأحكام الفقهيَّةَ المبنيَّة على العرف تتغيّر بتغيُّر هذا العرف؛ لتغيُّر المناط، وعدم تحقُّق علَّةِ الأصل في الفرع، الأمر الذي يُظهر مرونةَ الشريعة، وعدمَ الجمود على المنقول، وما إرسالُ الرسل، ولا إنزالُ الكتب، إ اَّ لتحقيق سعادة العباد في الدنيا والآخرة، والله ل الموفِّق والهادي إلى سواء السبيل.

Modern hayatın getirdiği vakalarla birlikte, ortaya çıkan bir olay için hüküm veren müçtehidin, içtihadında dayandığı şer’î esasları açıklamasını gerektiren yeni ve karmaşık fıkhî örneklere tanık olunmaktadır. Biz de bu çalışmamızda vakıayla çalışan müçtehidin kullandığı; şer’î hükümlerin illetlerini bulma, şâri’in niyetine muhalefet etmeme, mefasid ve masalih arasında denge kurma gibi fıkhî içtihadın değerini ve her zaman ve mekandaki sahaliyetini gösteren belli başlı fıkıh kaidelerine ışık tutmaya çalıştık. Araştırmamız sonucunda günümüzde ortaya çıkan fıkhî meselelerin şer’î asıllara hükmetmediği bilakis bu meselelerin, naslar ve şer’î kaideler çerçevesinde değerlendirildiği hakikati açığa çıkmıştır. Böylelikle fıkhî kaidelerin vakıaya boyun eğmediği ancak vakıanın fıhkî kaidelere boyun eğdiği görülmüştür. Geleneksel fıkıh mirası ile çağdaş fıkıh meseleleri arasında hem yenilenmeyi durdurmayacak hem de geleneği sarsmayacak bir denklem ile sağlam bir bağ kurulması gerekmektedir. Bunu yaparken zahir ve batını birleştirerek orta yolu bulan bir yönteme dayanılmalıdır. Aynı zamanda örfe dayanarak oluşturulan fıkhî hükümlerin, örfün veya teamülün değişmesiyle değişebileceği üzerinde durulmalıdır. Böylelikle şeriatın esnekliği ve naslar ile donuk olmadığı da açığa çıkmaktadır.

Nowadays, we are experimenting new patterns of Jurisprudence in the domain of Fiqh, that necessitate the illustration of the religious controls the jurist must respect when studying an emerging case. This research aims to highlight these controls that determine the basics of how to deal with the new emerging issues and cases in order to justify the legal provisions and not contradict the Legislator’s aims while establishing the equilibrium between right and wrongdoings. Furthermore, it will display the value of jurisprudence and the fact that the Sharia is applicable in ever time and place. The main outcome of this research shows that the emerging cases must be subject to the legal regulations of the Sharia, and there is no way to try to adapt texts to the issues, because these emerging issues must not control and restrict the texts, quite the contrary. On the other hand, a close link between the emerging case and the traditional regulations of jurisprudence (Fiqh) must be achieved by shaping a of equilibrium that doesn’t touch the fundamentals of the Sharia and doesn’t prevent the modernity. A moderated methodology must be adopted by harmonizing the appearance and the essence and displaying the fact that the dispositions built on the customs may be amended when customs and lifestyle change. This confirms the flexibility of the Sharia, and it is worthy to mention that the purposes of sending messengers, and holy books are to ensure the happiness of all mankind in this world and in hereafter.
Günümüz Fıkıh Meselelerinin Dayandığı Esaslar
The Contemporary Application of Islamic Jurisprudence Principles
Keywords: الواقع; التعليل; المقاصد; الاعتدال; الاجتهاد; العادة; Vakıa; İllet; Makasıd; İçtihad; Adet; İtidal; Actuality; Justification; Objectives; Moderation; Exertion; Habit